Evaluation of the results of the use of different types of autologous cartilage for restoration of structural support of the nose in secondary rhinoplasty - Fastovets, Ivan; Zaporozhets, Tetiana (ScienceRise: Medical Science, 2025)
According to the literature, from 14 to 50% of patients after primary rhinoplasty still require repeated interventions to correct aesthetic or functional defects of the nose, for which various types of autologous cartilage grafts are used. Despite the number of possible donor sites of autologous cartilage, their resorption still remains a significant problem in the context of the stability of long-term rhinoplasty results. Objective: To conduct a comparative assessment of the clinical results of using different types of autologous cartilage in secondary rhinoplasty. Materials and methods. A prospective study was conducted involving 54 patients aged 18 to 60 years who underwent secondary rhinoplasty in the period from January 2022 to January 2025 and who were divided into 3 groups according to the type of autologous cartilage. The study used questionnaires NOSE, ROE, VAS (satisfaction), photometry, and statistical research methods. Evaluations of the results were carried out at 3, 6, 12, 24, 36 months of follow-up. Results. Three months after the intervention, the median NOSE score was 35 points. The ROE level 3 months after the operation was characterized by a median of 62.5 points. During the following months, a gradual increase in this score was observed until the twelfth month. Regarding objective indicators, the width of the nose one year after the operation was 32.4 mm, the height of the nasal bridge - 4.7 mm, the projection of the nasal tip was recorded at 21.3 mm. The height of the bridge showed a tendency to decrease (to 4.0 mm after three years). Conclusions. The use of autologous cartilage grafts in secondary rhinoplasty provides a significant improvement in functional and aesthetic results without a statistically significant difference between the study groups. The process of cartilage resorption in all cases of rhinoplasty is progressive and correlates with the observation period. In our case, resorption was observed for the entire sample from 1.5% after one year to 2.3% after three years